Measuring and modeling salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
For almost three decades, the theory of visual attention (TVA) has been successful in mathematically describing and explaining a wide variety of phenomena in visual selection and recognition with high quantitative precision. Interestingly, the influence of feature contrast on attention has been included in TVA only recently, although it has been extensively studied outside the TVA framework. The present approach further develops this extension of TVA’s scope by measuring and modeling salience. An empirical measure of salience is achieved by linking different (orientation and luminance) contrasts to a TVA parameter. In the modeling part, the function relating feature contrasts to salience is described mathematically and tested against alternatives by Bayesian model comparison. This model comparison reveals that the power function is an appropriate model of salience growth in the dimensions of orientation and luminance contrast. Furthermore, if contrasts from the two dimensions are comb
Keywords: Salience; Visual attention; Bayesian inference; Theory of visual attention; Computational modeling; Inference; Object Recognition; Theories; Visual Perception; Visual Attention; Luminance; Perceptual Orientation; Statistical Probability; Stimulus Salience; Computational Modeling

Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Prior entry and temporal attention: Cueing affects order errors in RSVP. - Hilkenmeier, Frederic; Olivers, Christian N. L.; Scharlau, Ingrid (Journal of Experimental Psychology: Human Perception and Performance)
The law of prior entry states that attended objects come to consciousness more quickly than unattended ones. This has been well established in spatial cueing paradigms, where two task-relevant stimuli are presented near-simultaneously at two different locations. Here, we suggest that prior entry also plays a pivotal role in temporal attention paradigms, where stimuli appear at the same location but at distinct moments in time, in rapid serial presentation (RSVP). Specifically, we hypothesize that prior entry can explain temporal order reversals in reporting two targets from RSVP. In support of this, three experiments show that cueing attention toward either of the targets has a strong influence on order errors. We conclude that prior entry provides a viable explanation of the way in which relevant information is prioritized in RSVP. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: attentional blink; attentional enhancement; lag-1 sparing; prior entry; temporal cueing; visual attention; rapid serial presentation; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Female; Humans; Male; Neuropsychological Tests; Pattern Recognition; Visual; Time Factors; Visual Perception; Young Adult; Cues; Serial Recall; Visual Attention; Eyeblink Reflex

At the mercy of prior entry: Prior entry induced by invisible primes is not susceptible to current intentions. - Weiß, Katharina; Scharlau, Ingrid (Acta Psychologica)
If one of two events is attended to, it will be perceived earlier than a simultaneously occurring unattended event. Since 150 years, this effect has been ascribed to the facilitating influence of attention, also known as prior entry. Yet, the attentional origin of prior-entry effects¹ has been repeatedly doubted. One criticism is that prior-entry effects might be due to biased decision processes that would mimic a temporal advantage for attended stimuli. Although most obvious biases have already been excluded experimentally (e.g. judgment criteria, response compatibility) and prior-entry effects have shown to persist (Shore, Spence, & Klein, 2001), many other biases are conceivable, which makes it difficult to put the debate to an end. Thus, we approach this problem the other way around by asking whether prior-entry effects can be biased voluntarily. Observers were informed about prior entry and instructed to reduce it as far as possible. For this aim they received continuous feedback
Keywords: intentions; events; attention; decision processes; Adult; Attention; Choice Behavior; Cues; Female; Humans; Intention; Judgment; Male; Middle Aged; Reaction Time; Time Perception; Visual Perception; Attention; Decision Making; Experiences (Events); Intention

The dynamics of prior entry in serial visual processing. - Hilkenmeier, Frederic; Scharlau, Ingrid; Weiß, Katharina; Olivers, Christian N. L. (Visual Cognition)
An attended stimulus reduces the perceptual latency of a later stimulus at the same location, leading to the intriguing finding that the perceived order between the two is often reversed. This prior-entry effect has been well established in a number of different cueing paradigms, mostly involving spatial attentional shifts. Here we assess the time-course of prior entry when all stimuli appear in rapid serial presentation at one location. Our findings indicate that the size of the attentional enhancement is strongly affected by the stimulus onset asynchrony between cue and target, with a rapid early peak, followed by decay. When task-irrelevant cues are used, the cueing effect on prior entry is short-lived and peaks as early as 50 ms. The benefit extends to about 100 ms when task-relevant cues are employed. These results fit with a straightforward computational model of transient attentional enhancement, peaking about 80 100 ms after stimulus detection. (PsycINFO Database Record (c) 20
Keywords: serial visual processing; prior entry dynamics; cueing paradigms; Cues; Visual Perception; Visual Search

Top-down contingent feature-specific orienting with and without awareness of the visual input. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Advances in Cognitive Psychology)
In the present article, the role of endogenous feature-specific orienting for conscious and unconscious vision is reviewed. We start with an overview of orienting. We proceed with a review of masking research, and the definition of the criteria of experimental protocols that demonstrate endogenous and exogenous orienting, respectively. Against this background of criteria, we assess studies of unconscious orienting and come to the conclusion that so far studies of unconscious orienting demonstrated endogenous feature-specific orienting. The review closes with a discussion of the role of unconscious orienting in action control. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual input; awareness; conscious; orientation; visual perception; Awareness; Consciousness States; Perceptual Orientation; Visual Perception; Blindsight

Simultaneity and temporal order perception: Different sides of the same coin? Evidence from a visual prior-entry study. - Weiß, Katharina; Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology)
Attended stimuli are perceived as occurring earlier than unattended stimuli. This phenomenon of prior entry is usually identified by a shift in the point of subjective simultaneity (PSS) in temporal order judgements (TOJs). According to its traditional psychophysical interpretation, the PSS coincides with the perception of simultaneity. This assumption is, however, questionable. Technically, the PSS represents the temporal interval between two stimuli at which the two alternative TOJs are equally likely. Thus it also seems possible that observers perceive not simultaneity, but uncertainty of temporal order. This possibility is supported by prior-entry studies, which find that perception of simultaneity is not very likely at the PSS. The present study tested the percept at the PSS in prior entry, using peripheral cues to orient attention. We found that manipulating attention caused varying temporal perceptions around the PSS. On some occasions observers perceived the two stimuli as sim
Keywords: temporal order perception; simultaneity; temporal order judgment; attention; visual perception; Adolescent; Adult; Attention; Cues; Discrimination (Psychology); Female; Humans; Judgment; Male; Models; Psychological; Photic Stimulation; Reaction Time; Time Factors; Uncertainty; Visual Perception; Young Adult; Attention; Judgment; Stimulus Similarity; Time Perception; Visual Discrimination; Temporal Order (Judgment)

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Top–down contingent attentional capture during feed-forward visual processing. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Acta Psychologica)
Comments on an article by Jan Theeuwes (see record [rid]2010-20897-002[/rid]). Theeuwes summarizes an impressive number of studies demonstrating interference by irrelevant visual singletons in computer experiments with humans. Theeuwes assumes that this salience-driven capture of attention is fast and occurs within 150 ms since singleton onset, during the feed-forward phase of visual processing. In contrast to Theeuwes, we think that top–down contingent capture is the rule and explains initial and fast attention capture effects in the first feed-forward phase of visual processing. During a later phase and under some conditions exogenous capture of attention possibly follows. At the same time, we propose that the evidence presented by Theeuwes fails to support exogenous orienting because it fails to exclude a top–down contingent capture explanation. We present our arguments in two sections. One major source of evidence for top–down controlled attentional capture during the feed-forward
Keywords: visual selection; attention; information; visual field; brain; Attention; Humans; Models; Psychological; Visual Perception; Volition; Brain; Visual Field; Visual Perception; Visual Attention; Information

Temporal processes in prime-mask interaction: Assessing perceptual consequences of masked information. - Scharlau, Ingrid (Advances in Cognitive Psychology)
Visual backward masking is frequently used to study the temporal dynamics of visual perception. These dynamics may include the temporal features of conscious percepts, as suggested, for instance, by the asynchronous-updating model (Neumann, 1982) and perceptual-retouch theory (Bachmann, 1994). These models predict that the perceptual latency of a visual backward mask is shorter than that of a like reference stimulus that was not preceded by a masked stimulus. The prediction has been confirmed by studies using temporal-order judgments: For certain asynchronies between mask and reference stimulus, temporal-order reversals are quite frequent (e.g. Scharlau, & Neumann, 2003a). However, it may be argued that these reversals were due to a response bias in favour of the mask rather than true temporal-perceptual effects. I introduce two measures for assessing latency effects that (1) are not prone to such a response bias, (2) allow to quantify the latency gain, and (3) extend the perceptual e
Keywords: temporal processes; prime mask interaction; perceptual consequences; masked information; visual backward masking; visual perception; Temporal Lobe; Visual Masking; Visual Perception; Consequence

Experiments on the Fehrer-Raab effect and the 'Weather Station Model' of visual backward masking. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The Fehrer-Raab effect (simple reaction time is unaffected by metacontrast masking of the test stimulus) seems to imply that a stimulus can trigger a voluntary reaction without reaching a conscious representation. However, it is also possible that the mask triggers the reaction, and that the masked test stimulus causes a focussing of attention from which processing of the mask profits, thus reaching conscious representation earlier. This is predicted by the Weather Station Model of visual masking. Three experiments tested this explanation. Experiment 1 showed that the masked test stimulus caused a temporal shift of the mask. Experiment 2 showed that the reaction in the Fehrer-Raab effect was not exclusively triggered by a conscious representation of the test stimulus: the mask was involved in evoking the reaction. Experiment 3 again revealed a temporal shift of the mask. However, the shift was only about half as large as the Fehrer-Raab effect. The psychometric functions suggested tha
Keywords: Fehrer-Raab effect; Weather Station Model; visual backward masking; reaction time; metacontrast masking; conscious representation; Cognition; Humans; Perceptual Masking; Pilot Projects; Psychology; Experimental; Psychometrics; Reaction Time; Visual Perception; Models; Reaction Time; Visual Contrast; Visual Masking

Visual attention and the mechanism of metacontrast. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The U-shaped metacontrast function may result from the superimposition of two monotonic components which reflect the effects of mechanisms similar to the peripheral and central processes suggested for backward pattern masking by Turvey (Psychol Rev 80:1-52, 1973). In an experiment using the disc-ring paradigm, it was demonstrated that the decreasing and increasing branches of the metacontrast function are differently affected by the exposure duration of the mask and a task-irrelevant stimulus (distractor) appearing in the contralateral visual hemifield. The phenomenal representation of masking is different for the two parts of the curve. It is suggested that masking in the second part of the masking function, but not in the first, is related to the control of visual attention. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual attention; metacontrast; backward pattern masking; monotonic components superimposition; Attention; Contrast Sensitivity; Humans; Judgment; Perceptual Masking; Visual Perception; Metacognition; Visual Contrast; Visual Attention; Visual Masking

Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type. - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta Psychologica)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184-197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation w
Keywords: latency facilitation; temporal order judgments; visual processing; priming; conscious perception; visual mask; Adult; Attention; Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Space Perception; Time Perception; Visual Perception; Consciousness States; Judgment; Priming; Visual Masking; Temporal Order (Judgment)

More efficient rejection of happy than of angry face distractors in visual search. - Horstmann, Gernot; Scharlau, Ingrid; Ansorge, Ulrich (Psychonomic Bulletin & Review)
In the present study, we examined whether the detection advantage for negative-face targets in crowds of positive-face distractors over positive-face targets in crowds of negative faces can be explained by differentially efficient distractor rejection. Search Condition A demonstrated more efficient distractor rejection with negative-face targets in positive-face crowds than vice versa. Search Condition B showed that target identity alone is not sufficient to account for this effect, because there was no difference in processing efficiency for positive- and negative-face targets within neutral crowds. Search Condition C showed differentially efficient processing with neutral-face targets among positive- or negative-face distractors. These results were obtained with both a within-participants (Experiment 1) and a between-participants (Experiment 2) design. The pattern of results is consistent with the assumption that efficient rejection of positive (more homogenous) distractors is an im
Keywords: angry face distractors; visual search; negative face distractors; Adult; Anger; Attention; Face; Female; Happiness; Humans; Male; Rejection (Psychology); Visual Perception; Distraction; Face Perception; Visual Perception; Visual Search

Visual search for a motion singleton among coherently moving distractors. - Ansorge, Ulrich; Scharlau, Ingrid; Labudda, Kirsten (Psychological Research)
In the current study, we tested whether search for a visual motion singleton presented among several coherently moving distractors can be more efficient than search for a motion stimulus presented with a single distractor. Under a variety of conditions, multiple spatially distributed and coherently moving distractors facilitated search for a uniquely moving target relative to a single-motion-distractor condition (Experiments 1,3, and 4). Color coherencies among static distractors were not equally effective (Experiments 1 and 2). These results confirm that humans are highly sensitive to antagonistically directed motion signals in backgrounds compared with spatially more confined regions of visual images. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual search; motion singleton; visual images; visual motion; coherently moving distractors; Adult; Attention; Exploratory Behavior; Female; Humans; Male; Motion Perception; Visual Perception; Motion Perception; Stimulus Salience; Visual Search; Distraction; Retinal Image

Perceptual latency priming and illusory line motion: Facilitation by gradients of attention? - Scharlau, Ingrid; Horstmann, Gernot (Advances in Cognitive Psychology)
The phenomena of illusory line motion and perceptual latency priming are both assumed to reflect a facilitation of perceptual latency. The explanation of illusory line motion presupposes that attention is distributed in a gradient fashion whereas this is not a necessary part of the explanation of perceptual latency priming. Two experiments test whether an attentional gradient is present in perceptual latency priming. Evidence for a gradient was found within 2.5° of visual angle around the attended location, but not at a distance of 5° and more. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; illusory line motion; attention; visual angle; Illusions (Perception); Priming; Visual Field; Visual Perception; Visual Attention; Spatial Orientation (Perception)

Evidence against response bias in temporal order tasks with attention manipulation by masked primes. - Scharlau, Ingrid (Psychological Research)
Attending to a location shortens the perceptual latency of stimuli appearing at this location (perceptual latency priming). According to attentional explanations, perceptual latency priming relies on the speeded transfer of attended visual information into an internal model. However, doubts about the attentional origin have repeatedly been raised because efforts to minimize response bias have been insufficient in most studies. Five experiments investigated the contribution of a response bias to perceptual latency priming (judgment bias due to the two-alternative forced-choice method and due to the existence of the prime, criterion effects or second-order bias, sensorimotor priming). If any, only small response biases were found. The results thus support the attentional explanation. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: response bias; temporal order tasks; attention manipulation; masked primes; perceptual latency priming; Adult; Attention; Discrimination Learning; Female; Humans; Male; Memory; Short-Term; Orientation; Pattern Recognition; Visual; Perceptual Masking; Psychomotor Performance; Psychophysics; Reaction Time; Serial Learning; Attention; Latent Learning; Priming; Response Bias; Visual Perception; Response Latency; Temporal Order (Judgment)

The spatial distribution of attention in perceptual latency priming. - Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology A: Human Experimental Psychology)
The spatial distribution of visual attention is a yet unresolved question. One of the main topics is whether attention is distributed in a graded fashion around an attended location (e.g., Downing, 1988; Zimba & Hughes, 1987). The present experiments explore whether, and on which conditions, gradients of attention arise and contribute to perceptual facilitation. A masked or unmasked prime precedes one of two targets whose temporal order has to be judged. The prime captures attention, which shortens the perceptual latency of the primed target (perceptual latency priming; Scharlau & Neumann, 2003a; Shore, Spence, & Klein, 2001). No strong evidence for an attentional gradient was found. (1) Accuracy of temporal order judgements was independent of the distance between the two targets that were judged. That is, facilitation of the second target by the first target was spatially invariant. (2) With targets of short duration, facilitation was independent of prime-target distance. (3) With ta
Keywords: visual attention; spatial distribution; perceptual latency priming; Attention; Priming; Spatial Organization; Visual Perception

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Temporal parameters and time course of perceptual latency priming. - Scharlau, Ingrid; Neumann, Odmar (Acta Psychologica)
Visual stimuli (primes) reduce the perceptual latency of a target appearing at the same location (perceptual latency priming, PLP). Three experiments assessed the time course of PLP by masked and, in Experiment 3, unmasked primes. Experiments 1 (N=11; mean age 26.9) and 2 (N=12; mean age 25.6) investigated the temporal parameters that determine the size of priming. Stimulus onset asynchrony was found to exert the main influence accompanied by a small effect of prime duration. Experiment 3 (N=19; mean age 27.7) used a large range of priming onset asynchronies. We suggest to explain PLP by the Asynchronous Updating Model which relates it to the asynchrony of 2 central coding processes, preattentive coding of basic visual features and attentional orienting as a prerequisite for perceptual judgments and conscious perception. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: perceptual latency priming; temporal parameters; Asynchronous Updating Model; time course; stimulus onset asynchrony; visual masking; attention; Adult; Attention; Female; Humans; Male; Perceptual Masking; Reaction Time; Time Perception; Visual Perception; Attention; Priming; Stimulus Onset; Visual Masking; Visual Perception; Models; Time

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability

Leading, but not trailing, primes influence temporal order perception: Further evidence for an attentional account of perceptual latency priming. - Scharlau, Ingrid (Perception & Psychophysics)
Presenting a masked prime leading a target influences the perceived onset of the masking target. This priming effect is explained by the asynchronous updating model: The prime initiates attentional allocation toward its location, which renders a trailing target at the same place consciously available earlier. In 3 experiments, this perceptual latency priming by leading primes was examined jointly with the effects of trailing primes in order to compare the explanation of the asynchronous updating model with the onset-averaging and the P-center hypotheses. Exp 1 (n=15, mean age 27.1 yrs) showed that an attended, as well as an unattended, prime leads to perceptual latency priming. In addition, a large effect of trailing primes on the onset of a target was found. As Exp 2 (n=13, mean age 26.5 yrs) demonstrated, this effect is quite robust, although smaller than that of a leading prime. In Exp 3 (n=13, mean age 24.8 yrs), masked primes were used. Under these conditions, no influence of tra
Keywords: attention; leading primes; trailing primes; temporal order perception; perceptual latency priming; Adult; Attention; Female; Fixation; Ocular; Humans; Male; Perceptual Masking; Random Allocation; Time Perception; Visual Perception; Attention; Masking; Priming; Stimulus Frequency; Temporal Frequency; Temporal Order (Judgment)